Strategi Optimalisasi Kepuasan Masyarakat Pada Pelayanan Tenaga Kesehatan Masa Pandemi - Nurul Laili; Farida Hayati (STIKES dan AKZI Karya Husada Kediri, 2022)
Health services in health facilities have changed since the pandemic, such as health services currently focused on handling Covid-19 which has disrupted other health services and affected the level of community satisfaction due to changes in the current focus of health services. Satisfaction is a form of individual assessment of the services provided which is manifested as a feeling of pleasure. The purpose of community service activities is to provide education on how to use good and correct health services during a pandemic so that people feel satisfied with the health services provided by health workers. Education or counseling will be held on February 3-5, 2022, at RT 02 RW 07 Dusun Mlilir, Cikaran Village, Purwoasri District, Kediri Regency. The counseling participants who attended were 25 people. The number of students who participated in the activity was 2 students. The method used is lecture, discussion/question and answer using leaflet media, explanation of material using LCD and laptop media. The results of interviews and filling out questionnaires about satisfaction with health care services during the pandemic, it was found that almost half of the respondents had a high level of satisfaction, and a small portion had low satisfaction. The strategy is to realize patient satisfaction with the services provided through the characteristics, physical form, guarantee, care, and reliability factors of health workers. The COVID-19 pandemic has affected the health care system. The pandemic period requires a balance between the needs of handling the pandemic and the fulfillment of essential health services. Basic health services to the community are provided in a balanced manner for all disease conditions with the aim that when the pandemic is over there will be no increase in cases of chronic disease.